PIRIN2 stabilizes cysteine protease XCP2 and increases susceptibility to the vascular pathogen Ralstonia solanacearum in Arabidopsis - Zhang, B; Tremousaygue, D; Denancé, N; Van Esse, HP; Hörger, AC; Dabos, P; Goffner, D; Thomma, BPHJ; Van Der Hoorn, RAL; Tuominen, H (Wiley, 2014)
PIRIN (PRN) is a member of the functionally diverse cupin protein superfamily. There are four members of the Arabidopsis thaliana PRN family, but the roles of these proteins are largely unknown. Here we describe a function of the Arabidopsis PIRIN2 (PRN2) that is related to susceptibility to the bacterial plant pathogen Ralstonia solanacearum. Two prn2 mutant alleles displayed decreased disease development and bacterial growth in response to R. solanacearum infection. We elucidated the underlying molecular mechanism by analyzing PRN2 interactions with the papain‐like cysteine proteases (PLCPs) XCP2, RD21A, and RD21B, all of which bound to PRN2 in yeast two‐hybrid assays and in Arabidopsis protoplast co‐immunoprecipitation assays. We show that XCP2 is stabilized by PRN2 through inhibition of its autolysis on the basis of PLCP activity profiling assays and enzymatic assays with recombinant protein. The stabilization of XCP2 by PRN2 was also confirmed in planta. Like prn2 mutants, an xcp2 single knockout mutant and xcp2 prn2 double knockout mutant displayed decreased susceptibility to R. solanacearum, suggesting that stabilization of XCP2 by PRN2 underlies susceptibility to R. solanacearum in Arabidopsis.